University communities for the green/digital renovation of public buildings - Gisella Calcagno; Lucia Montoni (Techne)
In the face of climate change and energy crises, the renovation of existing buildings is an adaptation imperative. Despite ambitious policies, effective progress is hindered by a limited focus on financial returns, neglecting the broader social and environmental dimensions of renovations. This paper presents a university-driven Living Lab methodology experimenting with Digital Twins to foster collaboration and engagement in the co-design of ambitious renovation projects for public buildings. Tested in a pilot project site in a historical context, the research demonstrates the potential to optimise renovation processes and outcomes. Results highlight the transformative impact of the methodology, while addressing challenges for scaling up and replication.